2009
DOI: 10.1155/2009/701019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dysautonomias Comorbid with Cyclic Vomiting Syndrome and with Migraine

Abstract: Cyclic vomiting syndrome (CVS) shares many features with migraine headache, including auras, photophobia, and antimigrainous treatment response being traditionally viewed as a migraine variant. Aims. To determine whether CVS is associated with the same disorders as migraine headache, and compare these associations to those in healthy control subjects. Methods. Cross-sectional study of patients utilizing the ODYSA instrument, evaluating the probability of 12 functional/autonomic diagnoses, CVS, migraine, orthos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
3
30
1
Order By: Relevance
“…Additionally, the syncopal migraine group also has a significantly higher rate of QSART abnormalities. This finding was also reported in a prior study of another form of atypical migraine, cyclic vomiting syndrome [9].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the syncopal migraine group also has a significantly higher rate of QSART abnormalities. This finding was also reported in a prior study of another form of atypical migraine, cyclic vomiting syndrome [9].…”
Section: Discussionsupporting
confidence: 87%
“…The refl ex appears to be absent in Rodentia (e.g., laboratory rats and mice) and Lagomorpha (e.g., rabbits and hares) [ 12 ]. In Horn Cisplatin [ 54 , 55 ] Nicotine [ 109 ] Apomorphine [ 110 ] Morphine [ 111 ] Motion [ 112 ] 5-HT 1A CuSO4 [ 114 ] Cisplatin [ 114 ] Nicotine [ 114 ] Motion [ 113 ] H 1 histamine 1, M (3/5) et al, we tested representative members of the three main groups of rodents (mouse-related, Ctenohystrica, and squirrel-related) and none were found to have emetic responses to apomorphine, CuSO 4 , or veratrine (a plant alkaloid) [ 34 ]. Using an isolated perfused brainstem preparation, we also showed that laboratory rats and mice lack any coordinated neural efferent activity that would indicate emesis, compared to musk shrew controls [ 34 ].…”
Section: Why Do Some Animals Lack a Vomiting Refl Ex Circuit?mentioning
confidence: 99%
“…Altered serotonergic (5-HT) signaling has been postulated as a factor in IBS with increased circulating levels of 5-HT demonstrated in diarrheal-predominant IBS and decreased 5-HT levels in constipation-predominant IBS [ 109 ]. The importance of 5-HT in IBS is highlighted by the use of selective serotonergic agonists and antagonists in the treatment of different IBS phenotypes [ 110 ]. Alterations of the gut microbiome is also proposed to be an important factor in the pathophysiology of IBS with studies suggesting that IBS patients show an abundance of fi rmicutes and/or decrease in bacteroidetes bacteria [ 111 ].…”
Section: Functional Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid symptoms commonly experienced by patients with CVS include migraine headaches, anxiety, gut dysmotility (e.g., constipation), and postural orthostatic tachycardia syndrome, all of which are conditions associated with aberrant autonomic control. The autonomic nervous system plays an essential role in the responses to emetic activators.…”
Section: Introductionmentioning
confidence: 99%